(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
It is aimed to study the conditions of its historical development in order to understand the relations of the Anglo-Saxon and Romano-German legal system states regarding contracts, the nature of the legal consequences arising from non-fulfillment of contracts.